pls answer this with proper explaination pls
Attachments:
![](https://hi-static.z-dn.net/files/dc0/f1ec614c55700062026b0454131f2eb8.jpg)
Answers
Answered by
0
Answer:
option (1) 10b²
Step-by-step explanation:
4a²+5b²
+ (-4a²) + 5b²
=
4a²+5b²
-4a²+5b²
=
5b²+5b²(4a²-4a²=0)
=
10b²
Answered by
1
(4a^2+5b^2)+(-4a^2+5b^2)
= 4a^2-4a^2+5b^2+5b^2
=10b^2
option 1
Similar questions
English,
2 months ago
History,
2 months ago
Computer Science,
2 months ago
Science,
5 months ago
Business Studies,
1 year ago
Math,
1 year ago
Math,
1 year ago